Financial liberalisation and exchange rate inertia in Trinidad and Tobago - Henry, Lester ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Examines the related stability of the exchange rate in Trinidad and Tobago over the past five years. Expolores various possible explanations for this exchange rate inertia.